Development of cod farming in Norway: Past and current biological and market status and future prospects and directions. (22nd July 2021) - Puvanendran, Velmurugu; Mortensen, Atle; Johansen, Lill‐Heidi; Kettunen, Anne; Hansen, Øyvind J.; Henriksen, Edgar; Heide, Morten
Abstract: Atlantic cod is a historically abundant species in the North Atlantic region and has contributed to the prosperity of many nations. But a decline in stocks in the last century has prompted to initiate commercial farming of cod in captive conditions. Several approaches have been employed ranging from stock enhancement, capture‐based aquaculture and intensive cod farming. However, except for the enhancement efforts which were carried out for almost a century, efforts on other methods were intermittent coinciding with lower quotas. Intensive farming was attempted in Norway, Scotland, Ireland, Canada, Iceland and Faroe Islands in the 2000s. But it was carried out hastily to cash in the demand for cod in the market even though there were many biological knowledge gaps that are required for a successful aquaculture venture. The reasons for the failure of commercial farming in Norway during the 2000s were not only because of limited knowledge of the biology of cod but also the economic meltdown in Europe in 2008. Cod farming came to a halt; however, the Norwegian National Cod Breeding Program (NCBP) initiated in 2003 continued to operate and produced a fifth generation of a domesticated cod in 2019. Efforts to fill the gaps and the selective breeding for better growth and disease resistance within NCBP have improved the quality of the juveniles produced. We will discuss the past efforts and reasons for failure in farming of cod, how the current situation looks and the future direction in terms of cod biology, political atmosphere and market.